2013
DOI: 10.1016/j.visres.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small orientation changes and the precision of visual working memory

Abstract: We investigated the precision of orientation representations with two tasks, change detection and recall. Previously change detection has been measured only with relatively large orientation changes compared to psychophysical thresholds. In the first experiment, we measured the observers' ability (d') to detect small changes in orientation (5-30°) with 1-4 Gabor items. With one item even a 10° change was well detected (average d'=2.5). As the amount of change increased to 30°, the d' increased to 5.2. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…It has been shown that the ability to detect a change of the spatial frequency of a Gabor gating after a memory delay degraded with increasing number of stimuli (Wright et al 2000;Wilken and Ma 2004). In orientation reproduction tasks in which subjects had to reproduce a probe orientation within an array of previously presented orientation stimuli, a monotonic was observed similar to our study (Wilken and Ma 2004;Salmela and Saarinen 2013). In contrast to our prediction (see "Introduction"), the increasing delay time in experiment 1 had no effect on orientation accuracy.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been shown that the ability to detect a change of the spatial frequency of a Gabor gating after a memory delay degraded with increasing number of stimuli (Wright et al 2000;Wilken and Ma 2004). In orientation reproduction tasks in which subjects had to reproduce a probe orientation within an array of previously presented orientation stimuli, a monotonic was observed similar to our study (Wilken and Ma 2004;Salmela and Saarinen 2013). In contrast to our prediction (see "Introduction"), the increasing delay time in experiment 1 had no effect on orientation accuracy.…”
Section: Discussionsupporting
confidence: 49%
“…c σ (modeling the SD of the orientation error) for all subjects plotted against stimulus orientation as predicted from the GAMLSS model applied to the data set of experiment 1. Line colors correspond to number of presented targets 1: black, 2: red, 3: green and 4: blue and different line shapes correspond to different presentation times (1 s: solid, 2 s: log-dashed, 5 s: two-dashed and 7 s: dotted) (color figure online) of visual orientations from working memory, target presentation time was either varied depending on the number of items in the array assuming a constant viewing time per item (Salmela and Saarinen 2013) or was constant independent of the number of items in the array to be remembered (Wilken and Ma 2004). In our first experiment, we kept this time constant.…”
Section: Discussionmentioning
confidence: 99%
“…The task used orientation stimuli that were designed to: (a) equate the discriminability of two targets that could be separately cued, (b) elicit variation in the accuracy of responses and RTs as a function of set size and (c) maximise competitive interactions within VWM by requiring observers to search for targets defined by different values from a single feature-dimension [24], [28]. Displays contained rectangular stimuli that subtended 2.5° by 0.5° of visual angle.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research, however, has revealed that increasing the number of objects in VWM reduces the precision with which they are maintained [22][24]. In the standard signal detection framework, d’ is determined by two parameters; the distance between the distributions associated with the target and the distractors and the common standard deviation of these distributions [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation